PENOLAKAN KLAIM ASURANSI JIWA KARENA TIDAK DIUNGKAPKANNYA RISIKO KESEHATAN - Jamalum Sinambela (Fiat Iustitia : Jurnal Hukum, 2025)
The rejection of life insurance claims due to the insured’s failure to disclose health conditions often leads to legal disputes between insurance companies and beneficiaries. This study aims to analyze the legal basis for claim rejection under Article 251 of the Indonesian Commercial Code (KUHD) and the application of the good faith principle in life insurance contracts. The research employs a qualitative method with a normative juridical and case study approach, examining an actual claim rejection case by Prudential and several court decisions. The findings indicate that concealing material facts about health conditions constitutes a valid legal ground for insurers to reject claims. However, the role of insurance agents, transparency of information, and policyholder education are crucial in ensuring balanced legal protection for both parties. This study recommends strengthening regulations and establishing a more transparent risk verification system to prevent future disputes.